2013
DOI: 10.3109/08830185.2013.834899
|View full text |Cite
|
Sign up to set email alerts
|

Functional Plasticity of Th17 Cells: Implications in Gastrointestinal Tract Function

Abstract: The gastrointestinal tract is an active player of the human immune system, participating in the innate and adaptive immune responses, keeping the homeostasis of the human being in a healthy status. However, most intestinal conditions are associated with an altered immune response, which implies the activation of CD4(+) T helper (Th) cells. Based on their cytokine secretion, transcription factor expression and immunological functions, the differentiated Th cells were initially subdivided into different lineages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 132 publications
0
15
0
1
Order By: Relevance
“…Similar to the in vitro experiments, the high-salt diet promoted intestinal IL-17 production in CIA mice. IL-17 is primarily secreted from Th17 cells, although there are a few cell populations that express IL-17 in the intestine 20. Therefore, the presence of IL-17 in the intestinal tract of CIA mice fed a high-salt diet may indicate that the salt component promotes Th17 differentiation in the intestines.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the in vitro experiments, the high-salt diet promoted intestinal IL-17 production in CIA mice. IL-17 is primarily secreted from Th17 cells, although there are a few cell populations that express IL-17 in the intestine 20. Therefore, the presence of IL-17 in the intestinal tract of CIA mice fed a high-salt diet may indicate that the salt component promotes Th17 differentiation in the intestines.…”
Section: Discussionmentioning
confidence: 99%
“…Localized irradiation induces epithelial breakdown, immune cell accumulation, and activation of various compartments of the colon, leading to the secretion of several pro‐inflammatory molecules, including IL1β and TGFβ. These cytokines have been implicated in TH17 differentiation and could explain the increase of IL17 after irradiation . Various studies have analysed the critical role of IL17 in the development of pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance to intestinal I/R injury in IL-17A-depleted mice and IL-17A knock-out mice [30] indicated that targeting IL-17A to eliminate the higher number of infiltrating neutrophils into local tissues may be a promising therapy for I/R injury. However, as mentioned above, IL-17A is crucial for effective immune responses against commensal bacteria and pathogens in the intestine [31,32]. The simple depletion of IL-17A may induce severe side effects such as infection and bacterial translocation [31,33] and limit clinical trials.…”
Section: Abstract: Intestinal Ischemia/reperfusion Injury • Neutrophimentioning
confidence: 99%